EFFECT OF THE REGIONAL CLIMATE CHANGE ON RUNOFF FROM THE LAKE ONEGO WATERSHED (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
As a result of the statistical analysis of the meteorological and water balance data for Onego Lake watershed over the period 1950-2000, noticeable changes were detected. It was found that time series of annual air temperature, precipitation and evapotranspiration over 50-year period contains positive linear trends, but no change in total streamflow to the lake has so far followed. Potential changes in the regional climate and hydrological regime for the period 2000-2050 were estimated using the results of numerical modeling with the ECHAM4/OPYC3 model for two scenarios of the global climate change. The estimation of these data shows that a general tendency to increase of annual air temperature and precipitation will remain in the new climate Mean annual precipitation will increase about 30-50 mm, mean average annual air temperature for the next 50-years period will rise from 1.6 up to 2.7-3.0 °C. Our estimation shows that for both scenarios all water balance parameters, excluding river runoff, will increase.